CONTEMPORARY SYNERGIES BETWEEN THEATRE AND ENVIRONMENTAL HUMANITIES: «THE DOM-Project» - Fuoco , Ester (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
This study explores the nexus of urban dance and the environmental humanities, spotlighting the innovative Italian «DOM-project «Porpora che cammina» as a paradigmatic example of how contemporary theatrical practices are weaving ecological awareness into the urban landscapes. By scrutinizing the integration of mesology and eco-sustainability within performing arts, the paper investigates how urban environments transform into vibrant stages that interrogate the relationships among individuals, society and urbanity. Drawing on the principles of Richard Schechner's «Environmental Theatre» and Maurice Merleau-Ponty's phenomenological approach, as well as emerging aesthetic theories, the research highlights the importance of embodied experience and audience engagement in redefining perceptions of urban spaces. It also emphasizes the need for a prismatic and interdisciplinary analysis, no longer confined solely to theatre studies. The «DOM-project» serves as a case study to illustrate the dynamic interplay between permanence and transience in urban settings, offering insights into the ways artistic practices can foster a deeper connection with the environment. This inquiry highlights the role of performative arts in promoting environmental consciousness, demonstrating the potential of «site-specific theatre» and urban dance to redefine spectatorship and enhance our engagement with the urban ecosystem.